1996
DOI: 10.1080/15216549600201922
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of chitinase from cabbage stems with roots

Abstract: Chitinase has been purified from the extract of cabbage stems with roots through successive steps of ammonium sulfate fractionation, Sephadex G‐75 gel filtration, chromatofocusing and Sephacryl S‐200 HR gel filtration. By these steps, the purity of the enzyme increased by 63 fold and the recovery of the enzyme activity was 18%. The purified enzyme was homogeneous when analyzed by SDS‐PAGE#. It showed an optimal pH of 6 and optimal temperature of 60°C for hydrolysis of ethylene glycol chitin (EGC). The molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…Result of the screening experiments indicated that the enzymatic activity was varied not only with the species of the tested plants, but also according to the morphology of the examined parts. These results are to great extent in accordance to those found by Powning and lrzykiewicz (1965), Abeles et al (1971), Hirano et al (1990), Leah et al (1991) and Chang et al (1996). The increase in activity of chitinase during germination may be due to activation of the latent form and for increase in the rate of de novo synthesis of enzymes.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Result of the screening experiments indicated that the enzymatic activity was varied not only with the species of the tested plants, but also according to the morphology of the examined parts. These results are to great extent in accordance to those found by Powning and lrzykiewicz (1965), Abeles et al (1971), Hirano et al (1990), Leah et al (1991) and Chang et al (1996). The increase in activity of chitinase during germination may be due to activation of the latent form and for increase in the rate of de novo synthesis of enzymes.…”
Section: Discussionsupporting
confidence: 80%
“…The molecular weight of the purified chitinase was determined to be 64×10 3 . Concerning the M,s of chitinase enzyme isolated from different sources, it was found to be different, as chitinase isolated from bean leaves, soybean seeds, cabbage stem with root and tomato stem tissue have M,s range from 27×10 3 to 31×10 1 Dalton (Pegg and Young, 1982;Wadsworth and Zikakis, 1984;Chang et al, 1996). It was found that the M,s of stomach of Japanese eel, Bacillus, cereus, Serratia marcescens and S. peculiarities chitinase were 59×10 3 , 68.52×10 3 , 58×10 3 and 45×10 3 Dalton respectively (Kono et al, 1990;Zhang et al, 1996: Porfir'eva et al, 1997.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations